SURAT DAKWAH NABI MUHAMMAD SAW (ANALISIS TEMATIK ATAS SURAT-SURAT NABI MUHAMMAD KEPADA PARA RAJA) - Ubaidillah Ubaidillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
This paper aims to find the themes of propagation of Islam Prophet Muhammad in the early spread of Islam that can be used uswah hasanah by preachers in Indonesia in spreading Islam in accordance with the present context. Letters were used as the data in this study are the letters sent by the Prophet Muhammad to the king superpower in the Roman and Persian kings and their little under the authority of the king of the superpower. The letters are including in these types of letter are ten letters. Stanton thematic theory which states that the theme (theme) is contained in the meaning of a story, become the basic theory in this study. In addition, there is also a theme in the study of the distribution of known theme with theme of major and minor themes. In analyzing the data, before entering the core analysis, the author uses the method of analysis and match with sub-method translational match. In this case, the letters of the Prophet Muhammad first translated into Indonesian, after it analyzed according issues to be answered. The findings of this thematic analysis form the major theme of â€œpropagation of Islamâ€ whose content is tailored to the circumstances of the king recipients. Of the major themes, there are minor themes are used to support the universality of the major themes of these letters, they are: dakwah must be by the name of God, pray forsalvation only to Muslims, Jesus is not the son of God, all the religions of Semitic is unity of God (tawhid), religion God recognized only Islam, and Islam is tolerant religion.Â Tulisan ini bertujuan untuk mencari tema-tema dakwah Islam Nabi Muhammad pada awal penyebaran Islam yang dapat dijadikan uswah hasanah oleh para daâ€™i di Indonesia dalam menyebarkan agama Islam yang sesuai dengan konteks kekinian. Surat yang dijadikan data pada penelitian ini adalah surat-surat yang dikirim oleh Nabi Muhammad kepada para raja adidaya di Romawi dan Persi beserta raja-raja kecil yang berada di bawah kekuasaan kedua raja adidaya tersebut. Yang temasuk dalam jenis surat ini sejumlah sepuluh pucuk surat. Teori tematik Stanton dan Kenny yang menyatakan bahwa tema (theme) adalah makna yang dikandung sebuah cerita, menjadi landasan teori dalam penelitian ini. Selain itu, terdapat pula pembagian tema yang dalam kajian tema dikenal dengan tema mayor dan tema minor. Dalam menganalisis data, sebelum masuk pada analisis inti, penulis menggunakan metode analisis padan dengan submetode padan translasional. Dalam hal ini, surat-surat Nabi Muhammad tersebut diterjemahkan terlebih dahulu ke dalam bahasa Indonesia, setelah itu dianalisis sesuai permasalahan yang ingin dijawab. Temuan dari analisis tematik ini berupa tema mayor tentang â€œdakwah Islamâ€ yang isinya disesuaikan dengan keadaan para raja penerima surat. Dari tema mayor tersebut, terdapat tema-tema minor yang digunakan untuk mendukung keuniversalan tema mayor surat-surat tersebut, yaitu berdakwah harus karena Allah, mendoakan keselamatan hanya untuk muslim, Nabi Isa bukananak Tuhan, seluruh ajaran agama semitik adalah pengesaan Allah, agama yang diakui Allah hanya Islam, dan Islam agama yang toleran.